Differences in anatomy and potential hydraulic conductivity between root and stem of Caesalpinia echinata Lam. (Fabaceae) - Longui,Eduardo Luiz (2012)
We investigated the root and stem wood of Caesalpinia echinata Lam. to test the hypothesis that there are anatomical and water conductivity differences between both organs. Three trees about 20 years old were sampled in the Reserva Biológica de Mogi Guaçu, São Paulo State, Brazil. We observed quantitative anatomical differences between the root, heartwood, and sapwood of C. echinata that result in differences in water conductivity. The sapwood has higher potential hydraulic conductivity than the heartwood (when functional), and root. The higher proportion of axial parenchyma in the root could contribute to the storage of starch and water in unfavorable periods, which is important to the osmotic regulation of the daily water deficits, avoiding cavitation. The stem of C. echinata probably has a higher mechanical strength than the root due to its fibers with thicker wall.